The correlation between body mass index and the incidence of osteoarthritis in menopausal women - A.Rezki Nabila Syahrani; Masita Fujiko M. Said; Arina Fathiyyah Arifin; M. Hamsah; Fadil Mula Putra (International Journal of Health Science and Technology, 2025)
Osteoarthritis is more common in menopausal women due to decreased estrogen levels, which impacts joint health. Due to the high prevalence of OA in menopausal women with a high BMI, this study was conducted to determine the correlation between BMI and the incidence of OA in this group. The purpose of this study is to identify the correlation between Body Mass Index (BMI) and the incidence of osteoarthritis in menopausal women at Sinjai District Hospital during July-September 2024 period. This study applied an observational analytical design with a cross-sectional approach. The sample consisted of 50 menopausal women selected through consecutive sampling techniques. Data were collected through interviews, direct BMI measurements, and medical record reviews. Analysis was performed univariately and bivariately using the Chi-Square test. Based on the univariate analysis involving 50 respondents, it showed that most OA patients had an obese BMI (46%), while the normal category was only found in 26% of patients. Bivariate analysis using the Chi-Square test showed a significant relationship between BMI and OA (p-value = 0.007, p < 0.05). These results indicate that post-menopausal women with a BMI > 25 (obese category) have a higher risk of developing OA compared to those with a normal BMI. Conclusion: The conclusion of this study is that there is a significant relationship between BMI and OA in postmenopausal women, in which obesity is an important risk factor. This study recommends public education about the importance of maintaining ideal body weight as an effort to prevent OA in postmenopausal women, as well as the need for further research to explore the role of estrogen hormone levels in the pathogenesis of osteoarthritis.